Manejo de la plataforma virtual nearpod como un recurso tecnológico en los niños del cuarto año de educacion general básica en la Escuela Pedro Vicente Maldonado en la ciudad de Pujilí - Bedón Herrera, Dora Giovanna (2015)
The general objetive about this research is to propose the use of the Nearpod virtual platform as a technological resource that it allows to improve the academic and research activities in the students of fourth year at Pedro Vicente Maldonado school in Pujilí, due to the teachers don`t use the Nearpod virtual platform as a technological resource. The methods used were: the inductive in the analysis, interpretation and formulation of conclusions also for the development of justification; the deductive method in the verification of scientific question and helped in the development of the research review , The results about are that teachers don´t use Web 2.0 to teach their classes and activities are repetitive, students have the opportunity to interact his speech becomes mechanized. As conclusion that changes in technology invite teachers and students to resort to using Nearpod as input in the process of teaching - learning as a pedagogical and didactic classes mechanism.